The role of plant species and soil condition in the structural development of the rhizosphere - Helliwell, Jon R. (Plant Cell Environ, 2019)
Roots naturally exert axial and radial pressures during growth, which alter the structural arrangement of soil at the root–soil interface. However, empirical models suggest soil densification, which can have negative impacts on water and nutrient uptake, occurs at the immediate root surface with decreasing distance from the root. Here, we spatially map structural gradients in the soil surrounding roots using non‐invasive imaging, to ascertain the role of root growth in early stage formation of soil structure. X‐ray computed tomography provided a means not only to visualize a root system in situ and in 3‐D but also to assess the precise root‐induced alterations to soil structure close to, and at selected distances away from the root–soil interface. We spatially quantified the changes in soil structure generated by three common but contrasting plant species (pea, tomato, and wheat) under different soil texture and compaction treatments. Across the three plant types, significant increases in porosity at the immediate root surface were found in both clay loam and loamy sand soils and not soil densification, the currently assumed norm. Densification of the soil was recorded, at some distance away from the root, dependent on soil texture and plant type. There was a significant soil texture × bulk density × plant species interaction for the root convex hull, a measure of the extent to which root systems explore the soil, which suggested pea and wheat grew better in the clay soil when at a high bulk density, compared with tomato, which preferred lower bulk density soils. These results, only revealed by high resolution non‐destructive imagery, show that although the root penetration mechanisms can lead to soil densification (which could have a negative impact on growth), the immediate root–soil interface is actually a zone of high porosity, which is very important for several key rhizosphere processes occurring at this scale including water and nutrient uptake and gaseous diffusion.